Franchir l’infranchissable – stratégies d’interaction orale en classe de FLE - Kucharczyk, Radosław (Studia Romanica Posnaniensia, 2011)
In this article I will show that oral interaction is an independent competence in the language learning / teaching process and it requires adequate strategies. At the beginning of the article, I will present a description of a spoken language and verbal oral interaction as a subject of linguistic studies. Next, I will present a description of oral interaction in accordance with The Common European Framework of Reference for Languages (CEFR), as well as, a description of the interactive strategies presented by the authors of the Framework. After that, I will present the place of oral interaction strategies in various administrative documents regulating learning / teaching foreign languages at present. The last part of the article will describe examples of didactic actions which had an objective of developing this strategic competence among the beginner students of Romance philology.